Integracijski programi za priseljence v izbranih državah Evropske unije - Bešter, Romana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
Integration programs for immigrants in selected EU member states. This article provides an overview and comparison of (introductory) integration programs for immigrants in selected EU Member States. The comparative study is based on analysis of relevant legal documents of selected countries, but also on information obtained from secondary sources. It focuses in particular on the following questions: Does the country have integration programs for immigrants? What contents do they cover? Who are the target groups of these programs? Who bears the costs of organization and participation in the integration programs? Is participation in the integration programs mandatory or voluntary? Does the State encourage the participation of immigrants in the integration programs? Are there sanctions for nonparticipation? The article briefly presents also the legal-political framework of the EU in the field of immigrant integration. The author of this article notes that the introductory integration programs, which usually include learning the language of the host country and getting to know its culture and the legal and social arrangements,are a relatively new element in the integration policies of most countries studied. In other countries, where introductory integration programs have already existed for some time, a trend towards making these programs ever more restrictive can be noticed.
Keywords: European Union; Evropska unija; imigranti; integracija; družbena integracija; integracijski programi